2007
DOI: 10.1111/j.1365-2567.2006.02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of Fas (CD95) expression in tumour cells in vivo

Abstract: SummaryBoth the function and regulation of Fas expression in tumours is poorly understood. Our laboratory has reported that cultured, low Fas-expressing tumours undergo massive, yet reversible, up-regulation of cell surface Fas expression when injected into mice. The present study was aimed at determining what causes this enhanced Fas expression and whether the newly expressed Fas functions as a death receptor. Newly expressed Fas is indeed capable of inducing apoptosis. Based on our observation that Fas induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
(127 reference statements)
1
14
0
Order By: Relevance
“…Recent articles reported that endogenous NO promotes oncogenesis and angiogenesis in various cancers (20,21). In contrast, other studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (22)(23)(24)(25)(26)(27)(28). These studies suggest that NO can act either as a tumor suppressor or as a tumor enhancer depending on cell type and the level of NO in the cells.…”
Section: Introductionmentioning
confidence: 98%
“…Recent articles reported that endogenous NO promotes oncogenesis and angiogenesis in various cancers (20,21). In contrast, other studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (22)(23)(24)(25)(26)(27)(28). These studies suggest that NO can act either as a tumor suppressor or as a tumor enhancer depending on cell type and the level of NO in the cells.…”
Section: Introductionmentioning
confidence: 98%
“…Recent papers reported that endogenous NO promotes oncogenesis and angiogenesis in various cancers (Ambs et al, 1998;Camp et al, 2006). In contrast, other studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (Chawla-Sarkar et al, 2003;Jarry et al, 2004;Kalivendi et al, 2001;Kotamraju et al, 2007;Notas et al, 2006;Peshes-Yaloz et al, 2007;Wang et al, 2003). These studies suggest that NO can act either as a tumor suppressor or a tumor enhancer depending on cell type and the level of NO in the cells.…”
Section: Roles For No In Cancermentioning
confidence: 73%
“…In contrast to the aforementioned effects of NO, other studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (Chawla-Sarkar et al, 2003;Jarry et al, 2004;Kalivendi et al, 2001;Kotamraju et al, 2007;Notas et al, 2006;Peshes-Yaloz et al, 2007;Wang et al, 2003). Nitrosylcobalamin (NO-Cbl), an analog of vitamin B12 that delivers nitric oxide (NO) and xhibits anti-tumor activity; NOCbl increases the expression of tumor necrosis factor-related apoptosis-inducing ligand (Apo2L/TRAIL) and its receptors, resulting in apoptosis of human tumors.…”
Section: Anti-cancer Effectsmentioning
confidence: 94%
“…Recent papers reported that endogenous NO promotes oncogenesis and angiogenesis in various cancers (12,13). In contrast, other studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (14)(15)(16)(17)(18)(19)(20)(21). These studies suggest that NO can act either as a tumor suppressor or as a tumor enhancer depending on cell type and the level of NO in the cells.…”
Section: Introductionmentioning
confidence: 70%
“…In addition, Yasukawa et al reported that NO directly modifies Akt protein and inhibits its activity (11). Recent studies have shown that NO inhibits cell proliferation and induces apoptosis in various cells including cancer cells, in vitro and in vivo (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%